Building an Information Security Awareness Program. Issue 5 (May 2015) - Unknown
Abstract : The most vulnerable part of your network is the people who use it. No matter how much money and effort you've expended implementing technology-based defences, one ill-judged click can be your undoing. This is well understood by security professionals – so why are organisations still so bad at communicating the security message to their staff?